APPLICATION OF CALCIUM BIOLEACHING BACTERIA FOR BIOPRECIPITATION AND BIOMINERALISATION OF CALCIUM CARBONATE (CACO3) IN INCREASING THE MICP (MICROBIALLY INDUCED CALCIUM CARBONATE PRECIPITATION) PROCESS FOR MATERIAL STRENGTH - Alexius Sitompul, Johannes
The issue of soil stability is a problem that will be faced by Indonesia with increasing of development in Indonesia. Indonesia has a number of steel plants that produce large amounts of slag. There are several bacteria that can process the metallurgical waste into soil strengthening materials to address the issue of soil stability. Microbially Induced Calcium Carbonate Precipitation (MICP) can be a solution for the utilization of metallurgical waste and at the same time addressing the issue of soil stability. Calcium needed in the MICP process is obtained through the bioleaching process by bioleaching bacteria.